England's Elizabeth : an afterlife in fame and fantasy - Dobson, Michael, 1960- (Oxford University Press, 2002)
No monarch is more glamorous or more controversial than Elizabeth I. The stories by which successive generations have sought to extol, explain, or excoriate Elizabeth supply a rich index to the cultural history of English nationalism - whether they represent her as Anne Boleyn's suffering orphan or as the implacable nemesis of Mary, Queen of Scots, as learned stateswoman or as frustrated lover, persecuted princess or triumphant warrior queen. This book examines the many afterlives the Virgin Queen has lived in drama, poetry, fiction, painting, propaganda, and the cinema over the four centuries since her death, from the aspiringly epic to the frankly kitsch. Exploring the Elizabeths of Shakespeare and Spenser, of Sophia Lee and Sir Walter Scott, of Bette Davis and of Glenda Jackson, of "Shakespeare in Love" and "Blackadder II", this is a lively, lavishly-illustrated investigation of England's perennial fascination with a queen who is still engaged in a posthumous progress through the collective pysche of her country
Keywords: Elizabeth -- I, -- Queen of England, -- 1533-1603 -- In literature.; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- In art.; Elizabeth -- I, -- Queen of England, -- 1533-1603; English literature -- History and criticism.; Great Britain -- History -- Elizabeth, 1558-1603 -- Historiography.; Literature and history -- Great Britain.; Monarchy in literature.; Queens in literature.; Littérature anglaise -- Histoire et critique.; Grande-Bretagne -- Histoire -- 1558-1603 (Élisabeth Ire) -- Historiographie.; Littérature et histoire -- Grande-Bretagne.; ART -- Reference.; ART -- Performance.; English literature; Historiography; Literature; Literature and history; Monarchy in literature; Queens in literature; Great Britain; 1558-1603; History; Art; Criticism, interpretation, etc.